The impact of oil price shocks on macroeconomic indicators: Evidence from four ASEAN countries - Adawiya Taufani; Dedi Budiman Hakim; Widyastutik Widyastutik (Economic Journal of Emerging Markets, 2022)
Purpose ― This study examines the impact of oil price shocks on macroeconomic indicators, namely real GDP, real exchange rates, inflation, real interest rates, the balance of payments, and unemployment rates in four ASEAN countries, namely Brunei Darussalam, Malaysia, Indonesia, and Thailand. Methods ― This research uses a Vector Error Correction Model (VECM). The oil price variable in this study was divided into two, namely, the increase and decrease in oil prices based on the Mork transformation. Findings ― The analysis showed that the impact of price increases tended to encourage the economy of Brunei Darussalam and Malaysia. The shock of falling oil prices tended to cause a decline in the economy of Brunei Darussalam and Malaysia. The shock of rising prices tended to hamper the economies of Indonesia and Thailand. The shock of falling oil prices did not always positively impact the economy of the importing country, especially for the balance of payments. Implication ― These results show that price shocks will produce different economic responses. Understanding a country's macroeconomic framework is important before implementing effective policies. Originality ― These results expand the literature on the impact of oil price shocks on macroeconomic indicators in developing countries and small open economies, while studies related to macroeconomics generally focus on growth and inflation. This study also distinguishes oil price shocks into rising and falling oil price shocks using the Mork transformation.